Being a teacher educator : research-informed methods for improving practice - Swennen, Anja; White, Elizabeth (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This collection offers a timely and wide-ranging contribution to the research-informed improvement of the work of teacher educators. Drawing on original research studies conducted across a range of European countries, Canada, and Israel, contributors offer insight not only into questions of curriculum and program development, research, and professional development, but into their day-to-day experience as teacher educators, student teachers, and mentors in schools. Themes explored include teaching and working with students, teacher educators as researchers, the partnership work of teacher educators, the professional development needs of teacher educators, professional development approaches for improving teacher education, and teacher educator empowerment. Arising from the international community of ATEE (the Association of Teacher Educators in Europe), and drawing together theory and practice, this book offers a unique survey of the contributions of teacher educators and charts a path for future directions of the field"--
OCLC-licensed vendor bibliographic record.
Keywords: Teachers -- Training of; Teachers -- In-service training; Teacher educators; Educational change; EDUCATION / Research